SOME METHODS OF ADAPTIVE MULTILAYER NEURAL NETWORKS TRAINING - Makhnist, Leonid; Maniakov, Nikolaj; Maniakov, Nikolaj (International Journal of Computing, 2014)
Is proposed two new techniques for multilayer neural networks training. Its basic concept is based on the gradient descent method. For every methodic are showed formulas for calculation of the adaptive training steps. Presented matrix algorithmizations for all of these techniques are very helpful in its program realization.